114 Pain and objectively measured cognitive performance in adults with multiple sclerosis: a systematic review. Issue 9 (12th August 2022) - Brown, Fraser; Glasmacher, Stella; Taylor, Daniel; Jenkins, Ruth; Chandran, Siddharthan; Gillespie, David; Foley, Peter
Abstract : Background: Pain and cognition are important symptoms in multiple sclerosis (MS). Cognitive processes contributing to pain experience are increasingly documented. Any relationship between pain and objectively measured cognitive performance (OMCP) in MS, including potential mediating factors such as fatigue and medication, remains unclear. Understanding this relationship may facilitate targeted treatment strategies. Objective: Determine the relationship between pain and OMCP in MS. Methods: We conducted a systematic review, following a pre-registered protocol, of clinical studies examining relationships between pain and OMCP in MS. We searched MEDLINE, Embase and PsychInfo. We assessed confounders and described findings using neuropsychologist-assigned cognitive domains. Risk of bias was assessed using a modified Newcastle-Ottawa Scale. Results: 10 studies were included. Eight studies identified a relationship between pain and OMCP. In six studies, worse pain scores were associated with worse cognition. However, no evidence was available for several cognitive domains. Studies infrequently controlled for confounders. Most studies were judged to be at risk of bias. Conclusions: While several studies suggest that pain in MS is related to worse objective cognitive perfor- mance, conclusions are limited by study design and limited evidence in many cognitive domains. Future studies should better establish this relationship and delineate the neurological substrate underpinning it.